Drug-Drug Interactions With Antiviral Agents in People Who Inject Drugs Requiring Substitution Therapy. (July 2015) - Meemken, Leonie; Hanhoff, Nikola; Tseng, Alice; Christensen, Stefan; Gillessen, Anton
Objective: To describe potential drug-drug interactions in the area of HIV/hepatitis C virus (HCV) coinfection and injection drug use, including those between antiretrovirals (ARVs), direct-acting antivirals (DAAs), and opioid-agonist therapy, and to supply a practical approach to their management.Data Sources: We searched PubMed for relevant articles published up until February 2015 as well as conference reports and drug-drug-interaction Web sites.Data Selection and Data Extraction: We used the following search terms: pharmacokinetic and pharmacodynamic drug-drug interaction, opioid substitution, HIV, hepatitis and the individual names of the relevant agents of the following drug classes and the drug classes itself: reverse transcriptase inhibitors, nonnucleoside reverse transcriptase inhibitors, protease inhibitors, direct-acting antivirals, opioide, benzodiazepines, anticonvulsants, antidepressants and antipsychotics . Additional references were identified from a review of literature citations and drug-drug interaction Web sites. In our evaluation, we included German- and English-language studies and reports addressing drug-drug interactions between opioid agonist therapy and ARVs or DAAs.Data Synthesis: Pharmacokinetic data were available for all ARVs and DAAs except rilpivirine, indinavir, saquinavir, maraviroc, dolutegravir, and MK-8742 with buprenorphine as well as maraviroc with methadone Drug-drug interactions of potential clinical relevance are most likely to occur between opioid-replacement therapy and ARVs, particularly the nonnucleoside reverse transcriptase inhibitors, efavirenz and nevirapine, and HIV protease inhibitors.Conclusion: Integrase inhibitors may be safely coadministered with opioid-replacement therapy. With respect to HCV DAAs, most currently approved and late-stage investigational agents do not have clinically significant interactions with opioid-replacement therapy. ARV and DAAs may interact with other drug classes commonly used in the opioid-dependent population, including benzodiazepines, antidepressants, anticonvulsants, and antipsychotics.